Pengaruh Rasio Likuiditas dan Pembayaran Deviden Terhadap Profitabilitas Perusahaan - Ernawati Ernawati; Ella Anastasya Sinambela (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Several countries in the world are experiencing a financial crisis. This incident caused them to need funds from other parties so that the company's operations could run smoothly. Investments can be made between countries as well as organizations such as the IMF or the world bank. To attract the attention of investors to want to invest in a company, a high profitability value is needed in the company. The company's management has an intensive attention to increase the company's profitability. The profitability of the company can be seen from the level of liquidity of the company. In addition, the policy of dividend distribution will reflect the level of company profitability. The purpose of this study was to determine the role of liquidity ratios and dividend payments in the formation of company profitability. The object of research is several companies in East Java. The number of research samples are respondents. The research data obtained will be served by SPSS using multiple linear regression analysis. The results showed that profitability got a significant role from the liquidity ratio partially. dividends also play a significant role in the company's profitability. The company's profitability simultaneously gets a significant role by the liquidity ratio and dividend payments